Fossil hydrocarbons chemistry and technology - Berkowitz, Norbert (Academic Press, 1997)
Berkowitz integrates material often found in standard professional handbooks on this subject, with discussion and examples that make for a readable work for professionals and students...a major goal of the book, and one that Berkowitz is successful in delivering, is for the reader to recognize that the future of heavy hydrocarbons is not merely a function they can be prepared, processed, and converted into products."